Comparison of DNA sequencing and morphological identification techniques to characterize environmental fungal communities - Naohide Shinohara (Nature Portfolio, 2021)
Abstract Culture-independent DNA sequencing of fungal internal transcribed spacer 2 (ITS2) region was compared to a culture-dependent morphological identification technique to characterize house dust-borne fungal communities. The abundant genera were Aspergillus, Wallemia, Cladosporium, and Penicillium. Statistically significant between-method correlations were observed for Wallemia and Cladosporium (Spearman’s ρ = 0.75 and 0.72, respectively; p < 0.001). Penicillium tended to be detected with much higher (averaged 26-times) relative abundances by the culture-based method than by the DNA-based method, although statistically significant inter-method correlation was observed with Spearman’s ρ = 0.61 (p = 0.002). Large DNA sequencing-based relative abundances observed for Alternaria and Aureobasidium were likely due to multicellularity of their spores with large number of per-spore ITS2 copies. The failure of the culture-based method in detectiing Toxicocladosporium, Verrucocladosporium, and Sterigmatomyces was likely due to their fastidiousness growth on our nutrient medium. Comparing between the two different techniques clarified the causes of biases in identifying environmental fungal communities, which should be amended and/or taken into consideration when the methods are used for future fungal ecological studies.